Теоретичні аспекти побудови когнітивної моделі ресурсного потенціалу зв’язано-диверсифікованої системи будівельних організацій в процесі аналізу стратегічних альтернатив - Лагутін, Г. В. (Ways to Improve Construction Efficiency, 2012)
This paper proposes the research of the model of the strategic management of the industrial plants scale activity, built by cognitive modelling.